1972
DOI: 10.1016/0005-2795(72)90174-2
|View full text |Cite
|
Sign up to set email alerts
|

The complete amino acid sequence of the basic nuclear protein of bull spermatozoa

Abstract: SUMMARYThe complete amino acid sequence of the basic nuclear protein of bull spermatozoa has been established. The sequence was partially deduced by characterization of peptides isolated from thermolysine and chymotryptic digests of the reduced and Saminoethylated protein. The complete sequence of the first 37 residues was determined by Edman-Begg degradation (Sequenator) of the protein. The amino acid sequence of the last 8 residues was determined by manual Edman degradation of an octapeptide obtained on clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…79:177a, 1978), rats (20,21), bulls (10,32,36), boars (36,43), rams (29,36,41), stallions (36), guinea pigs (8,9), rabbits (8,9), and humans (2,12,25,33,39). Complete sequence analysis of the P1 protamines from bulls (10,32), boars (43), rams (41), and humans (2,33) and the predicted amino acid sequence derived from a cDNA sequence for mouse protamine 1, (mPl) (24) have revealed identical lengths of 50 amino acids and strong sequence homologies among these mammalian protamines. P1 protamine is organized into three domains consisting of a central basic core with clusters of arginine and two less basic amino-and carboxyl-terminal regions.…”
mentioning
confidence: 99%
“…79:177a, 1978), rats (20,21), bulls (10,32,36), boars (36,43), rams (29,36,41), stallions (36), guinea pigs (8,9), rabbits (8,9), and humans (2,12,25,33,39). Complete sequence analysis of the P1 protamines from bulls (10,32), boars (43), rams (41), and humans (2,33) and the predicted amino acid sequence derived from a cDNA sequence for mouse protamine 1, (mPl) (24) have revealed identical lengths of 50 amino acids and strong sequence homologies among these mammalian protamines. P1 protamine is organized into three domains consisting of a central basic core with clusters of arginine and two less basic amino-and carboxyl-terminal regions.…”
mentioning
confidence: 99%
“…Electrophoretic and chromatographic analyses of these proteins have shown that the sperm of certain animals contain multiple protamine amino acid sequence variants and that the number of these variants differs from species to species. The sperm of bulls (24), rams (55,56), and rats (20,50), for example, contain only one protamine variant, whereas mouse sperm have two (6,9) and the sperm of humans (20,78) and certain fish (3) contain three different protamines.…”
mentioning
confidence: 99%
“…Although comparisons of the amino acid sequence of bull protamine (24) and the partial sequences of rat (50), boar (69), ram (69), stallion (69), human (34), and mouse (9) protamine indicate that the homology between various mammalian protamines is extensive, the primary structure of fish and mammalian protamines differs considerably . Mammalian protamines all contain a centrally located polyarginine stretch very similar in size to the entire length of the fish protamine, with additional nonbasic amino acid residues located in the 000H-terminal and N112-terminal "tail" fragments.…”
mentioning
confidence: 99%
“…Early studies of mammalian species indicated that there was a shift toward an arginine-rich nucleoprotein during spermiogenesis, and indeed several workers have isolated small basic proteins from spermatozoa. Coelingh et al isolated and sequenced a protein of molecular weight about 6000 from bull spermatozoa which contained large amounts of arginine and cysteine (7,8). Kistler et al have described another nuclear protein (MW about 6200) isolated only from mature rat testes, but which is not present in rat spermatozoa (9,10).…”
mentioning
confidence: 99%